2015
DOI: 10.1177/0032258x15585250
|View full text |Cite
|
Sign up to set email alerts
|

Highway informal policing in Kajola Local Government, Oyo State, Nigeria

Abstract: Informal policing continues to play a crucial role in the Nigerian security sector in spite of the fact that certain government agencies have been formally charged with the responsibility for crime prevention, detection and control. In view of this, this paper examines the origin, mode of operation and challenges of highway informal policing in Kajola Local Government. The study was anchored on routine activity theory. Data were principally generated through key informant interview and focus group discussion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A major implication of this result is that the existence of these challenges may make it very difficult for the affected communities to totally eliminate the occurrence of banditry within their localities because these situations are directly and indirectly aiding the activities of individuals engaging in acts constituting criminal victimisation. This output is in tandem with Ojedokun and Aderinto’s (2015) study which found the major challenges confronting some informal policing outfits that were securing the major inter-community highways in some rural localities in Oyo State as including inadequate access to weapons, poor funding and lack of access to some vital work-equipment. It also confirms the submission of SCP theory that society plays a role in inadvertently creating a crime through the manufacturing of “criminogenic goods”, through leaky systems and through poor management/design of facilities which consequently lead to the reduction of the risk and efforts that are necessary for crime perpetration while also simultaneously increasing the rewards that are associated with it.…”
Section: Challenges Associated With the Adopted Counter-banditry Stra...mentioning
confidence: 61%
“…A major implication of this result is that the existence of these challenges may make it very difficult for the affected communities to totally eliminate the occurrence of banditry within their localities because these situations are directly and indirectly aiding the activities of individuals engaging in acts constituting criminal victimisation. This output is in tandem with Ojedokun and Aderinto’s (2015) study which found the major challenges confronting some informal policing outfits that were securing the major inter-community highways in some rural localities in Oyo State as including inadequate access to weapons, poor funding and lack of access to some vital work-equipment. It also confirms the submission of SCP theory that society plays a role in inadvertently creating a crime through the manufacturing of “criminogenic goods”, through leaky systems and through poor management/design of facilities which consequently lead to the reduction of the risk and efforts that are necessary for crime perpetration while also simultaneously increasing the rewards that are associated with it.…”
Section: Challenges Associated With the Adopted Counter-banditry Stra...mentioning
confidence: 61%
“…Parole is the release of a prisoner from imprisonment before the full sentence is served by the parolee, on the grounds of good behavior Oromareghake, 2018). It is a period of discretionary/ conditional supervised release from prison (Ojedokun and Aderino, 2015). The parole system as a non-custodial measure can be traced to the 20 th century when indeterminate sentencing dominated the American jurisprudence (Ladapo, 2011).…”
Section: Parolementioning
confidence: 99%